2014
DOI: 10.1051/orthodfr/2014027
|View full text |Cite
|
Sign up to set email alerts
|

La recherche de l’excellence en orthodontie de l’adulte : entretien avec Bjørn U. Zachrisson

Abstract: Bjørn U. Zachrisson est Professeur Émérite au sein du Département d’Orthodontie de l’Université d’Oslo (Norvège). Il conserve à Oslo une pratique libérale consacrée aux traitements de l’adulte. Il a rédigé plus de 270 articles cliniques et scientifiques, publiés dans des revues internationales et dans des manuels d’orthodontie, de parodontologie, de traumatologie et de dentisterie générale. Il a représenté l’orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…This is consistent with the findings of the current study, where the noncrowding group (erupted third molars) had significantly larger values of the space/third molar width ratio than the crowded group (unerupted third molars). Zachrisson 30 noted that mandibular incisor crowding is often caused by a developing mandibular third molar with insufficient space, and a mesially directed force can contribute to early mandibular arch crowding. This is consistent with our study, as the authors found an insufficient retromolar space in the crowding group, where the Ganss ratio values were smaller than in the noncrowding group.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of the current study, where the noncrowding group (erupted third molars) had significantly larger values of the space/third molar width ratio than the crowded group (unerupted third molars). Zachrisson 30 noted that mandibular incisor crowding is often caused by a developing mandibular third molar with insufficient space, and a mesially directed force can contribute to early mandibular arch crowding. This is consistent with our study, as the authors found an insufficient retromolar space in the crowding group, where the Ganss ratio values were smaller than in the noncrowding group.…”
Section: Discussionmentioning
confidence: 99%
“…PA : La prise en compte explicite de l'esthétique du visage au sein d'un modèle centré sur les tissus mous représente un changement de paradigme récent 1 . Bjørn U. Zachrisson 172 , Renato Cocconi et Mirco Raffaini 39 ont montré, lors de leurs invitations aux précédentes conférences de prestige de la SFODF, pourquoi, comment l'esthétique de la face, plutôt que la seule occlusion, devrait guider la définition de nos objectifs thérapeutiques, dont le corolaire est un recours plus fréquent à la chirurgie orthognathique. Quelle approche préconisez-vous et quelle est la place de la chirurgie orthognathique dans votre enseignement ?…”
Section: Dtm Et Chirurgie Orthognathiqueunclassified